Desain Berkelanjutan Sebagai Upaya Pengembangan Kemasan Anyaman Bambu Khas Bali - Ni Luh Desi In Diana Sari; Ni Ketut Pande Sarjani; Gede Bayu Segara Putra; I Kadek Surya Wijaya Putra; Yogi Nur Ardiansyah (Institut Seni Indonesia Denpasar, 2022)
The Bali Provincial Government through PERGUB (Governor Regulation) Number 97 of 2018 has regulated the Limitation of Disposable Waste Generation. The implementation of these regulations has been implemented among Small and Medium Industries (IKM) that produce Balinese souvenirs. The IKM sector has begun to switch to using bamboo packaging, which is commonly used to package banten pejati (Balinese traditional offerings) sold in traditional markets. However, this condition causes the appearance of food packaging designs that package Balinese souvenirs to look uniform, lacking a touch of local Balinese culture that can be used as an identity for Bali's superior products branding to tourists. This creation aims to design bamboo packaging as Balinese souvenir packaging which has the concept of eco-friendly design. The research method was used to formulate the motif design concept and the method of creation to design the bamboo packaging design by adopting the woven bamboo technique at the bamboo craft center in Bali. The novelty of this bamboo packaging design can be seen in the motif design inspired by Geringsing Cemplong weaving motif which is formed with the woven bamboo technique. This motif has never existed before and is able to represent the identity of the local Balinese culture. The color material used as paint is a natural color material. Derived from mixing mango leaves and strobilanthes/indigo leaves through an environmentally friendly process to produce a green color. The creation of environmentally friendly bamboo packaging is expected to inspire woven-bamboo craftsmen to start switching to environmentally friendly products that are safe to use in food packaging.